2013
DOI: 10.1073/pnas.1219004110
|View full text |Cite
|
Sign up to set email alerts
|

GPR37 and GPR37L1 are receptors for the neuroprotective and glioprotective factors prosaptide and prosaposin

Abstract: GPR37 (also known as Pael-R) and GPR37L1 are orphan G protein-coupled receptors that are almost exclusively expressed in the nervous system. We screened these receptors for potential activation by various orphan neuropeptides, and these screens yielded a single positive hit: prosaptide, which promoted the endocytosis of GPR37 and GPR37L1, bound to both receptors and activated signaling in a GPR37- and GPR37L1-dependent manner. Prosaptide stimulation of cells transfected with GPR37 or GPR37L1 induced the phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
237
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(264 citation statements)
references
References 77 publications
11
237
5
Order By: Relevance
“…Conceivably, Gpr37l1 may be important in the activation of developing cerebellar glia, via still unknown ligands, whose production is temporally limited to the peri-and postnatal stages. Recently, the secreted neuro-and glioprotective glycoprotein prosaposin and derived peptides have been shown in vitro to activate the putative Gpr37l1 and Gpr37 receptors (22). Prosaposin and other secreted proteins are produced by Purkinje neurons of newborn mice, with very low expression in prenatal and adult stages (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceivably, Gpr37l1 may be important in the activation of developing cerebellar glia, via still unknown ligands, whose production is temporally limited to the peri-and postnatal stages. Recently, the secreted neuro-and glioprotective glycoprotein prosaposin and derived peptides have been shown in vitro to activate the putative Gpr37l1 and Gpr37 receptors (22). Prosaposin and other secreted proteins are produced by Purkinje neurons of newborn mice, with very low expression in prenatal and adult stages (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…G-protein-coupled receptors for the endothelin and bombesin peptides (17,20,21). Recently, the secreted neuro-and glioprotective glycoprotein prosaposin and derived peptides have been shown in vitro to interact with and activate both putative receptors (22).…”
mentioning
confidence: 99%
“…Based on these early findings, the research on GPR37 has mainly focused on strategies to improve its plasma membrane trafficking and to reduce the receptor-induced cell toxicity (Dunham et al, 2009;Gandía et al, 2013;Lundius et al, 2013;Dutta et al, 2014). Recently, GPR37, together with its closest homolog GPR37-like 1 (GPR37L1; Valdenaire et al, 1998), has been reported to act as a receptor for prosaposin and a prosaposin-derived peptide prosaptide (Meyer et al, 2013). These peptides, which possess neuroprotective and glioprotective effects (reviewed in Meyer et al, 2013), have been found to induce receptor internalization and to stimulate GPR37-mediated signalling in HEK293 cells and primary cortical astrocytes (Meyer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Gpr37, like Gpr17, can couple to Gα i/o proteins [65], cAMP levels are accordingly elevated in Gpr37-/-brains and cultured oligodendrocytes, and pharmacological experiments implicate increased Epac/Raf/ERK signaling downstream of cAMP when Gpr37 function is lost [59]. Although prosaponin has been identified as a ligand for Gpr37 [65], this glycoprotein may not function in Gpr37-mediated oligodendrocyte development [64]. Thus, identification of binding partner(s) for Gpr37 in oligodendrocyte lineage cells is an important area of future research.…”
Section: Oligodendrocyte Developmentmentioning
confidence: 99%
“…While Gpr17 and Gpr37 act at different stages, importantly, both GPCRs negatively regulate oligodendrocyte development: as in Gpr17 mutants, loss of Gpr37 leads to precocious oligodendrocyte differentiation [59]. Moreover, Gpr37, like Gpr17, can couple to Gα i/o proteins [65], cAMP levels are accordingly elevated in Gpr37-/-brains and cultured oligodendrocytes, and pharmacological experiments implicate increased Epac/Raf/ERK signaling downstream of cAMP when Gpr37 function is lost [59]. Although prosaponin has been identified as a ligand for Gpr37 [65], this glycoprotein may not function in Gpr37-mediated oligodendrocyte development [64].…”
Section: Gpr17 and Gpr37 In Oligodendrocyte Differentiationmentioning
confidence: 99%